Review of Methods for Studying Viruses in the Environment and Organisms - Xinyue Wang; Tong Ma; Zhiyuan Chen; Yang Liu; Kexin Wang; Guangxiu Liu; Kesheng Li; Tuo Chen; Gaosen Zhang; Wei Zhang; Binglin Zhang (Viruses)
Recent decades have seen growing attention on viruses in the environment and their potential impacts as a result of global epidemics. Due to the diversity of viral species along with the complexity of environmental and host factors, virus extraction and detection methods have become key for the study of virus ecology. This review systematically summarises the methods for extracting and detecting pathogens from different environmental samples (e.g., soil, water, faeces, air) and biological samples (e.g., plants, animals) in existing studies, comparing their similarities and differences, applicability, as well as the advantages and disadvantages of each method. Additionally, this review discusses future directions for research in this field. The aim is to provide a theoretical foundation and technical reference for virus ecology research, facilitating further exploration and applications in this field.